The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.bios.2016.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CCL2 and CCR2 chemokine/receptor deficiencies on macrophage recruitment and continuous glucose monitoring in vivo

Abstract: The accumulation of macrophages (MΦ) at the sensor-tissue interface is thought to be a major player in controlling tissue reactions and sensor performance in vivo. Nevertheless until recently no direct demonstration of the causal relationship between MΦ aggregation and loss of sensor function existed. Using a Continuous Glucose Monitoring (CGM) murine model we previously demonstrated that genetic deficiencies of MΦ or depletion of MΦ decreased MΦ accumulation at sensor implantation sites, which led to signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Pharmacologic inhibition of MCP-1 or CCR2 effectively reduced the recruitment of macrophage into the interstitial compartment and improved tubulointerstitial damage (41,42).In diabetic animal models treated with STZ, deficiency of MCP-1 decreased the number of macrophage accumulation and prevented early diabetic renal injury (34,40). In agreement with these previous studies, we observed that upregulated renal MCP-1 expression was accompanied by increased macrophage infiltration in tubular interstitial in diabetic mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Pharmacologic inhibition of MCP-1 or CCR2 effectively reduced the recruitment of macrophage into the interstitial compartment and improved tubulointerstitial damage (41,42).In diabetic animal models treated with STZ, deficiency of MCP-1 decreased the number of macrophage accumulation and prevented early diabetic renal injury (34,40). In agreement with these previous studies, we observed that upregulated renal MCP-1 expression was accompanied by increased macrophage infiltration in tubular interstitial in diabetic mice.…”
Section: Discussionsupporting
confidence: 90%
“…MCP-1, a member of the CC chemokine family acting through its receptor CCR2 (38), is a critical factor in recruiting monocytes/macrophages into inflammation site (39). The expression of MCP-1 in tubular cells and urinary excretion of the protein were both upregulated in human and experimental diabetes, which coincided with macrophage infiltration in both glomeruli and interstitial and correlated with levels of albuminuria and renal function decline (34,37,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Increased OSM contributes to hepatic IR and the development of NASH (46). High levels of TNF-α released by M1-KCs stimulates hepatic expression of CCL2, a powerful monocyte chemoattractant, which recruits CCR2 + Ly6C high monocytes from the vasculature into the liver (47), where they differentiate into Ly6C high macrophages. The Ly6C high macrophages amplify the severity of obesity-induced inflammation and hepatic IR through secretion of TNF-α and IL-6 (48).…”
Section: Immune Cells and Their Polarization In Livermentioning
confidence: 99%
“…Increased OSM contributes to hepatic IR and the development of non-alcoholic steato hepatitis (NASH) (71). High levels of TNF-α released by M1-KCs stimulate hepatic expression of CCL2 (also known as MCP1), a powerful monocyte chemoattractant, which recruits CCR2 + Ly6C high monocytes from the vasculature into the liver (72), where they differentiate into Ly6C high macrophages. The Ly6C high macrophages amplify the severity of obesity-induced inflammation and hepatic IR through the secretion of TNF-α and interleukin 6 (IL-6) (12).…”
Section: Macrophage Regulation During Nafld/nashmentioning
confidence: 99%